IRC data for a mechanistic route starting with H2O adsorption and finishing with H2 desorption from graphene - Oyarzún Aravena, Andrea María; Garcia, Ximena; Radovic, Ljubisa (My University, 2020)
Intrinsic reaction coordinate (IRC) data regarding the interactions of water with a carbene-like active site located at the edge of a polyaromatic hydrocarbon [1-3] has been obtained using density functional theory (DFT) and the 6-31g(d) basis set as implemented in the Gaussian 16 software [4]. The data is presented as two videos (frontal and lateral mechanism views) combining four consecutive IRC calculations corresponding to the four different transition states presented on "https://doi.org/10.1016/j.carbon.2020.01.011" [3] (Figure 6, side approach). These videos provide powerful insights on two key aspects: a) the rotational process that occurs during water adsorption and b) the hydrogen gas desorption process during water gasification of carbons. (C) 2020 The Authors. Published by Elsevier Inc.
Keywords: water rotation; water adsorption; hydrogen desorption; water gasification; reaction mechanism; ab initio